BEBERAPA FAKTOR YANG MEMPENGARUHIPARTISIPASI NELAYAN DALAM PEMBANGUNAN KOMUNITAS DI TPI ASEMDOYONG, KABUPATEN PEMALANG, JAWA TENGAH - Waridin Waridin (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2007)
This study is aimed to describe the socioeconomic profiles of the fishers. This is also intended to analyse the degree and factors influencing fishers' participation in community development in Asemdoyong, Pemalang district.This study utilized primary and secondary data. By using quota sampling, a number of 100 fishers were selected as the sample of the study. Data analysis applied multiple regression and discriminant analysis.Results of the study verified that gender, education, and number of family were the variables which influenced the degree of fishers' participation while age and income did not influence significantly. In addition, age, gender, education, number of family, and income were the independent variables which able to discriminate the intensity of fishers participation.